Uncovering Embodied Community Cultural Wealth: Hung dee moy Brings Forth New Possibilities (LEARNing Landscapes, 2023)
In this paper, educators unpack their community cultural wealth, also known as hung dee moy 同姊妹, a Toisanese-Chinese sisterhood support system. I narratively inquire alongside my participants Felicia and Mary, uncovering their embodied experiences of hung dee moy knowledge, passed from their mothers to them and onto the next generation. In attending closely to their experiences as expressions of hung dee moy, their narratives illuminate the interconnections between micro and macro contexts, showing how patterns of race-based exclusion and interpersonal and institutional racism affected generations of Toisanese. Participants highlight the power of hung dee moy to cultivate collective strength through intergenerational resistance.This paper discusses the process of uncovering generational wealth and holds the possibilities of others articulating their ancestral knowledge.
Keywords: community cultural wealth; CCW; narrative inquiry; Asian American